2010
DOI: 10.4049/jimmunol.1000265
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Delay and Reversal of T Cell Tolerance by Intratumoral Injection of Antigen-Loaded Dendritic Cells in an Autochthonous Tumor Model

Abstract: The tumor environment exerts a powerful suppressive influence on infiltrating tumor-reactive T cells. It induces tolerance of adoptively transferred effector T cells as they enter tumors and maintains the tolerance of persisting tumor-infiltrating T cells. In an autochthonous prostate cancer model, in which tumor-reactive CD8 T cells are trackable, we demonstrate that both depletion of endogenous dendritic cells (DCs) and intratumoral injection of Ag-loaded mature DCs delayed the tolerization of tumor-infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…The observed difference was not due to differential retention of anti-CD70 treated BMDCs within the prostate tissue as compared to control treated BMDCs (Fig. 5 E ), consistent with previous experiments with untreated BMDCs (13). These results show that CD70/CD27 interaction is required for DC-mediated delay of 2C T cell tolerance induction in the prostate tumor tissue.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The observed difference was not due to differential retention of anti-CD70 treated BMDCs within the prostate tissue as compared to control treated BMDCs (Fig. 5 E ), consistent with previous experiments with untreated BMDCs (13). These results show that CD70/CD27 interaction is required for DC-mediated delay of 2C T cell tolerance induction in the prostate tumor tissue.…”
Section: Resultssupporting
confidence: 91%
“…3B). Previous work has shown that depletion of prostate DCs reverses 2C T cell tolerance (13). Considering that tolerance can result from pMHC presentation by DCs lacking costimulatory signals (32), these data suggest that steady-state prostate resident DCs promote T cell tolerance, perhaps through pMHC/TCR engagement without costimulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations